Analysis of Subsidy Arrangements in Indonesia in View of the SCM Agreement (Agreement on Subsidies and Countervailing Measures) - Darmawan Febri Padmono (PT FORMOSA CENDEKIA GLOBAL, 2023)
The rules that have been agreed upon in the WTO Agreement cover various matters or fields. One such agreement is subsidies and countervailing measures. The rules regarding subsidies and reward actions are actually one of the six main rules produced by the Tokyo Round. each signatory country must notify all subsidies, including all forms of income and price support, which affect directly or indirectly on increasing exports of all types of products or reducing imports of all types of products into the territory of Indonesia. Implementation of Subsidy Arrangements in International Trade in Indonesia is regulated through Government Regulation Number 34 of 1996 concerning Antidumping Duties and Compulsory Import Duties. These rules are in accordance with the applicable provisions, but related to cases that occurred in Indonesia, especially in the settlement of export subsidy disputes, this is not regulated in the SCM Agreement. The settlement of the dispute is regulated in Article XXII and Article XXIII WTO Article XXII in the GATT agreement requires the parties to resolve their disputes through bilateral consultations.